Analysis of Speech Acts in Conversations Between Characters in the Film “Good Will Hunting (1997)” - Aulia, Maqdis Fayza; Syathroh, Isry Laila (Siliwangi University, 2023)
Language is a crucial component of communication and serves as the foundation for interactions. In linguistics, there is a branch called pragmatics that studies speech acts. Pragmatics provides a framework for analyzing the relationship between language and context. Related to pragmatics, this research explores the classifications of speech acts in the film